Highly Efficient Base‐Free Dehydrogenation of Formic Acid at Low Temperature. Issue 18 (15th August 2018) - Prichatz, Christoph; Trincado, Monica; Tan, Lilin; Casas, Fernando; Kammer, Anja; Junge, Henrik; Beller, Matthias; Grützmacher, Hansjörg
Abstract: The ruthenium complex [RuH2 (PPh3 )4 ] is a competent catalyst for the selective dehydrogenation of formic acid (FA) at low temperature. It tolerates water and shows excellent performance (TOF up to 36 000 h −1 at 60 °C). Remarkably, no basic additives are necessary to obtain such high activity and the defined complex is stable for up to 120 days, making this system one of the most effective formic acid dehydrogenation catalysts known to date. Abstract : No bases in fact : The well‐known ruthenium complex [RuH2 (PPh3 )4 ] catalyzes the highly selective dehydrogenation of formic acid at low temperature. It tolerates water, shows excellent performance, and does not need any basic additives, rendering this system one of the most effective formic acid dehydrogenation catalysts known to date.